EXTERNAL OFFALS OF LOHMANN BROWN AGE 22 WEEKS FED RATION WITH DRAGON FRUIT SKIN (Hylocereus polyrhizus) FERMENTED - K. G. P., Muda; Dewi, G. A. M. K.; Wijana, I W. (Jurnal Peternakan Tropika, 2019)
This study aims to determine the effect of giving fermented dragon fruit skin (Hylocereus polyrhizus) to the external offals of Lohmann Brown22 weeks aged. This research has been carried out at theLaboratory (Teaching Farm) and Poultry Laboratory, Faculty of Animal Husbandry Bukit Campus, Jimbaran, Badung, Bali took place on 26 November – 26 December 2018. The chicken used was 18 weeks of laying hens Lohmann Brown of 45 birds. The design used was Completely Randomized Design (CRD) with three treatments and five replications namely control ration where chickens given fermented dragon fruit ration (RKBN0), rations with fermented dragon fruit skins as much as 5% (RKBN1), and commercial rations (RKBN2) Drinking water and feed are given in ad libitum . Variables observed were head weight, neck weight, blood weight, feather weight, and leg weight. The data obtained were analyzed using analysis of variance (ANOVA), if between treatments there were significant differences (P <0.05) followed by Duncan's multiple distance test (Steel and Torrie, 1993) assisted by the SPSS 22.0 program. The results showed that each variable head weight, neck weight, blood weight, feather weight, and leg weight in the RKBN0, RKBN1, and RKBN2 treatments were not significantly different (P> 0.05). It can be concluded that the rations with 5% fermented dragon fruit skin (RKBN1) and commercial rations (RKBN2) but does not affect of externaloffals (head weight, neck weight, blood weight, feather weight, and leg weight) of Lohmann Brown chickens 22 weeks aged.  Keywords : Lohmann Brown, external offals, dragon fruit skin, rations